Análise da expressão das proteínas KRAS, BRAF e MEK da via de sinalização intracelular mitogen activated protein kinases (MAPK) no carcinoma hepatocelular associado a hepatopatia crônica de diferentes etiologias - Serena Dáfne Carmo Silva (2018)
Introduction: hepatocellular carcinoma (HCC), a very aggressive cancer, common in adults, can be initiated by factors like infection with hepatitis B virus (HBV) and regeneration of the liver induced by chronic diseases. Only 30-40% of these tumors are diagnosed at initial stages, when curative treatments are potentially available. For advanced stages, treatments modalities still have poor responses, reinforcing the importance of studying the mechanisms of carcinogenesis of this tumor. Currently, one of the most studied signaling pathways involved in the development of HCC is the mitogen activated protein quinase (MAPK), which has an important activity on the cellular cycle. Studies indicate that some components of this signaling cascade act as oncogenes, which makes MAPK a target for new therapeutic agent development. The aim of this study is to qualitatively describe the expression of the MAPK’s proteins – K-Ras, B-Raf and MEK – in HCC associated with hepatopathies of different etiologies. Methods: 40 HCC samples from hepatopathies of different etiologies – HBV, hepatitis C virus (HCV) infection, alcoholic and cryptogenic liver diseases (10 samples of each) were analyzed by immunohistochemistry in order to investigate the expression of some MAPK pathway proteins – K-Ras, B-Raf and MEK – in samples of HCC and adjacent cirrhotic parenchyma. Results: most patients (77.5%) were male and the median age was 58 years. There was no difference between etiologic groups regarding the clinic and pathologic parameters studies. No difference in the frequency of expression of the target proteins was observed when comparing tumor and adjacent cirrhotic tissue. Comparing each etiologic group individually, there was no statistically difference regarding the frequency of strong/moderate labeling of the target proteins. An inverse association between B-Raf expression and vascular invasion was seen when compared viral and non-viral etiologic group. Moreover, this comparison evidenced more frequent expression of the K-Ras in the samples from the first group. Conclusion: an inverse association regarding B-Raf expression and vascular invasion, such as a more frequent K-Ras expression in viral instead of non-viral group, were seen. These findings lead to a reflection about the heterogeneity and complexity of hepatocarcinogenesis. However, further studies are needed to the better comprehension and evaluation of such events in the CHC development.